KOMBINASI PUPUK LIMBAH CAIR BIOGAS DENGANTRICHOKOMPOS TKKS TERHADAPPERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI MAIN NURSERY - Erlindawati Lumban Toruan; Hapsoh Hapsoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research to know about the effect combination of bioslurry fertilizer with Trichocompost TKKS and get the best combination for the growth of palm oil seedlings in main nursery. This research has done in the Experimental Field of Agriculture Faculty, Riau University, Jl. Bina Widya KM 12,5 Simpang Baru, Tampan, Pekanbaru from April until July 2016. This experiment using Completely Randomized Design (CRD) consists of 6 treatments and 4 replications, in order to obtain 24 units experiments, each unit consist of 2 plants. As the treatment: combination bioslurry fertilizer with Trichocompost TKKS (P) are: P1: 100 ml with 74,5 g, P2: 200 ml with 74,5 g, P3: 300 ml with 74,5 g, P4: 100 ml with 124,5 g, P5: 200 ml with 124,5 g, P6: 300 ml with 124,5 g. The parameter those observed: seedling height increment, hump diameter increment, number of leaf growth, leaf area, and root seedling volume. Data analyzed with Anova and DNMRT 5%. The outcome of experience showed that combination of bioslurry fertilizer with Trichocompost TKKS real effect on parameter seedling height increment, hump diameter increment, leaf area, and root seedling volume. Combination of 300 ml of bioslurry fertilizer with 124,5 g Trichocompost TKKS is the best combination of all parameters. Keywords:Bioslurry Fertilizer, Trichocompost TKKS, Palm Oil Seedling